Current Situation, Trend and Peak-Reaching Path of Low-Carbon Development of Water Transportation in Zhejiang Province - Lu Meng; Wei Yanhua; Lu Yilei; Zhou Yiying (E3S Web of Conferences)
This paper analyzes the development status and trends of the water transport industry in Zhejiang Province in detail, including port infrastructure and operation, ship transport, waterway infrastructure and operation and other aspects. Meanwhile, it summarizes the main achievements of low-carbon development in the water transport industry and discusses the situational requirements. The water transport industry in Zhejiang Province has made remarkable progress in infrastructure construction, optimization of transportation organization, and green and low-carbon transformation. However, it still faces challenges from multiple aspects such as climate change, national policies, and green transportation construction. Finally, the paper proposes the implementation path for carbon peaking in the water transport industry of Zhejiang Province, covering aspects such as upgrading transportation equipment, optimizing organizational coordination, providing infrastructure support, enhancing intelligent innovation, and activating the roles of the government and the market.